2022
DOI: 10.3390/vaccines10071064
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Humoral and Cellular Immunity after an Extended Primary Series with Heterologous Inactivated SARS-CoV-2 Prime-Boost and ChAdOx1 nCoV-19 in Dialysis Patients (ICON3)

Abstract: The durability of a three-dose extended primary series of COVID-9 vaccine in dialysis patients remains unknown. Here, we assessed dynamic changes in SARS-CoV-2-specific humoral and cell-mediated immunity at baseline, 3 months, and 6 months after the extended primary series in 29 hemodialyzed (HD), 28 peritoneal dialyzed (PD) patients, and 14 healthy controls. Participants received two doses of inactivated SARS-CoV-2 vaccine followed by a dose of ChAdOx1 nCoV-19 vaccine. At 6 months, median anti-RBD IgG titers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The progressive decrease in antibody titers over time after each vaccination dose is a cause for concern. Previous reports have shown that 3 to 6 months after initial vaccination and booster doses, significant anti-spike titer decline is observed in dialysis patients [ 12 , 24 ]. At present, individualizing additional dose prescriptions is probably the best strategy to obtain an optimal immune response, avoiding the risk of hyperstimulation and immune exhaustion [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The progressive decrease in antibody titers over time after each vaccination dose is a cause for concern. Previous reports have shown that 3 to 6 months after initial vaccination and booster doses, significant anti-spike titer decline is observed in dialysis patients [ 12 , 24 ]. At present, individualizing additional dose prescriptions is probably the best strategy to obtain an optimal immune response, avoiding the risk of hyperstimulation and immune exhaustion [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients on PD, SARS-CoV-2 vaccination has demonstrated to be safe and to promote early and strong seroconversion at least with the initial schedule (i.e., two doses of mRNA-based vaccines [BNT162b2, mRNA-1273] or ChAdOx1-S or one dose of Ad26.COV.2) [ 6 , 11 ]. However, anti-spike antibody titers in PD decrease over time, as is the case for other RRT patients, potentially leading to suboptimal protection against SARS-CoV-2 [ 12 , 13 ]. In this regard, a booster (or third) dose was considered early for these vulnerable patients.…”
Section: Introductionmentioning
confidence: 99%
“…Those may also have confounded the relationship between the numbers of COVID-19 vaccination and fatality outcomes. Although the immunogenicity induced by COVID-19 vaccinations generally wanes over time ( 33 , 34 ), this does not imply that clinical protection against severity or mortality from COVID-19 has diminished ( 29 ). In this study, we described changes in PD bag exchange patterns and the functional status of PD patients during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Another report in France also revealed that a booster vaccination with the BNT162b2 vaccine could substantially increase anti-SARS-CoV-2 spike protein antibodies in patients undergoing dialysis [ 48 ]. Similarly, a prospective study in Thailand indicated that booster vaccination should be considered in HD patients who received an extended primary vaccine series, since the humoral immunity against COVID-19 declined significantly six months after the three-dose primary vaccination in this population [ 29 ]. However, most existing studies have focused on the immunogenicity of booster vaccination, and its real-world benefits on the clinical outcomes of COVID-19 have less been investigated in the HD population, particularly in those receiving oral antiviral agents.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies have indicated that two-dose primary vaccination might not be sufficiently protective against SARS-CoV-2 variants in HD patients, and vaccine boosters could be helpful in sustaining immunity against COVID-19 in this vulnerable population [ 27 , 28 ]. Although an extended (three-dose) primary vaccine series can induce a more robust immune response against COVID-19 in immunocompromised patients, a rapid waning of immunity has been reported in the HD population after this vaccine regimen, which also suggests the roles of additional vaccine boosters in HD patients [ 29 , 30 ]. Apart from vaccination, outpatient pharmaceutical treatment is also a key element in the sustained management of COVID-19, which could improve clinical outcomes and ease the burden on the healthcare system [ 19 ].…”
Section: Introductionmentioning
confidence: 99%